Pengaruh Sistem Pemerintahan Berbasis Elektronik (SPBE) di Era Desentralisasi dan Otonomi Daerah di Kota Pangkal Pinang, Provinsi Kepulauan Bangka Belitung - Yanto, Febri; Tjenreng, Muhammad Baharuddin Zubakhrum (Pascasarjana STIE Amkop Makassar, 2025)
Digital transformation in the government sector is a necessity in facing the challenges of the globalization era and the industrial revolution 4.0. The Pangkal Pinang City Government has adopted Electronic-Based Government System (EBS) as a key strategy in strengthening decentralization and improving the efficiency of governance. However, the implementation of SPBE still faces significant obstacles, such as limited human resources, uneven technological infrastructure, and bureaucratic resistance to digital change. This study aims to analyze the effectiveness of SPBE implementation in supporting decentralization and regional autonomy and identify the challenges faced. Using a qualitative approach with a case study method, data was obtained through in-depth interviews, observation, and analysis of policy documents. The results showed that SPBE has improved transparency and administrative efficiency, although there are still barriers in technical and social aspects. A comparative study with e-government models in Estonia and South Korea revealed that the success of government digitalization depends on infrastructure readiness, integrated policies, and increased digital literacy. Therefore, increasing the capacity of human resources and strengthening digital policies are strategic steps in optimizing the implementation of SPBE in Pangkal Pinang City.